Expression of class II histone deacetylases in two mouse models of temporal lobe epilepsy. Issue 4 (28th December 2015) - Jagirdar, Rohan; Drexel, Meinrad; Bukovac, Anneliese; Tasan, Ramon O.; Sperk, Günther
Abstract: Epigenetic mechanisms like altered histone acetylation may have a crucial role in epileptogenesis. In two mouse models of temporal lobe epilepsy, we investigated changes in the expression of class II histone deacetylases (HDAC), a group of signal transducers that shuttle between nucleus and cytoplasm. Intrahippocampal injection of kainic acid (KA) induced a status epilepticus, development of spontaneous seizures (after 3 days), and finally chronic epilepsy and granule cell dispersion. Expression of class II HDAC mRNAs was investigated at different time intervals after KA injection in the granule cell layers and in sectors CA1 and CA3 contralateral to the site of KA injection lacking neurodegeneration. Increased expression of HDAC5 and 9 mRNAs coincided with pronounced granule cell dispersion in the KA‐injected hippocampus at late intervals (14–28 days after KA) and equally affected both HDAC9 splice variants. In contrast, in the pilocarpine model (showing no granule cell dispersion), we observed decreases in the expression of HDAC5 and 9 at the same time intervals. Beyond this, striking similarities between both temporal lobe epilepsy models such as fast decreases in HDAC7 and 10 mRNAs during the acute status epilepticus were observed, notably also in the contralateral hippocampus not affected by neurodegeneration. The particular patterns of HDAC mRNA expression suggest a role in epileptogenesis and granule cell dispersion. Reduced expression of HDACs may result in increased expression of pro‐ and anticonvulsive proteins. On the other hand, export of HDACs from the nucleus into the cytoplasm could allow for deacetylation of cytoplasmatic proteins involved in axonal and dendritic remodeling, like granule cell dispersion. HDAC 5 and HDAC 9 expression is highly increased in granule cells of the KA‐injected hippocampus and parallels granule cell dispersion. Both HDACs are thought to be targeted to the cytoplasm and to act there by deacetylating cytoplasmatic (e.g. cytosceleton‐related) proteins. Abstract : HDAC 5 and HDAC 9 expression is highly increased in granule cells of the KA‐injected hippocampus and parallels granule cell dispersion. Both HDACs are thought to be targeted to the cytoplasm and to act there by deacetylating cytoplasmatic (e.g. cytosceleton‐related) proteins.